Phenotypic diversity of circulating tumour cells in patients with metastatic castration‐resistant prostate cancer. (18th September 2016) - McDaniel, Andrew S.; Ferraldeschi, Roberta; Krupa, Rachel; Landers, Mark; Graf, Ryon; Louw, Jessica; Jendrisak, Adam; Bales, Natalee; Marrinucci, Dena; Zafeiriou, Zafeiris; Flohr, Penelope; Sideris, Spyridon; et al.
Abstract : Objectives: To use a non‐biased assay for circulating tumour cells (CTCs) in patients with prostate cancer (PCa) in order to identify non‐traditional CTC phenotypes potentially excluded by conventional detection methods that are reliant on antigen‐ and/or size‐based enrichment. Patients and Methods: A total of 41 patients with metastatic castration‐resistant PCa (mCRPC) and 20 healthy volunteers were analysed on the Epic CTC platform, via high‐throughput imaging of DAPI expression and CD45/cytokeratin (CK) immunofluorescence (IF) on all circulating nucleated cells plated on glass slides. To confirm the PCa origin of CTCs, IF was used for androgen receptor (AR) expression and fluorescence in situ hybridization was used for PTEN and ERG assessment. Results: Traditional CTCs (CD45 − /CK + /morphologically distinct) were identified in all patients with mCRPC and we also identified CTC clusters and non‐traditional CTCs in patients with mCRPC, including CK − and apoptotic CTCs. Small CTCs (≤white blood cell size) were identified in 98% of patients with mCRPC. Total, traditional and non‐traditional CTCs were significantly increased in patients who were deceased vs alive after 18 months; however, only non‐traditional CTCs were associated with overall survival. Traditional and total CTC counts according to the Epic platform in the mCRPC cohort were also significantly correlated with CTC counts according to the CellSearch system. Conclusions: Heterogeneous non‐traditional CTC populations are frequent in mCRPC and may provide additional prognostic or predictive information.